Learning materials and human factors: looking at the Chemistry in the genre-based approach classroom - Mahadhir, Mahanita; Ting, Su Hie; Carol, D. (Proceedings of 2nd Science and Art of Language in Teaching International Conference, 2006)
This action research project aims to find out how the genre-based approach worked with learners of limited English proficiency enrolled in an English for Social Purposes course focusing specifically on developing reading and writing skills. The course materials were designed using the genre-based approach and the concept of scaffolding. Instructors who taught the course in previous semesters were asked to compare the course materials with materials used in previous semesters, and to describe the delivery of their lessons and the strategies they used to achieve the purpose of the course. Students are also interviewed to find out their views on their language learning experience. The results provide some insights about the contribution of 'science' and 'art' into teaching language for specific purposes.